Human Three-Finger Protein Lypd6 Is a Negative Modulator of the Cholinergic System in the Brain - Kulbatskii, Dmitrii; Shenkarev, Zakhar; Bychkov, Maxim; Loktyushov, Eugene; Shulepko, Mikhail; Koshelev, Sergey; Povarov, Igor; Popov, Alexander; Peigneur, Steve; Chugunov, Anton; Kozlov, Sergey; Sharonova, Irina; et al. (Frontiers in Cell and Developmental Biology, 2021)
Lypd6 is a GPI-tethered protein from the Ly-6/uPAR family expressed in the brain. Lypd6 enhances the Wnt/β-catenin signaling, although its action on nicotinic acetylcholine receptors (nAChRs) have been also proposed. To investigate a cholinergic activity of Lypd6, we studied a recombinant water-soluble variant of the human protein (ws-Lypd6) containing isolated ‘three-finger’ LU-domain. Experiments at different nAChR subtypes expressed in Xenopus oocytes revealed the negative allosteric modulatory activity of ws-Lypd6. Ws-Lypd6 inhibited ACh-evoked currents at α3β4- and α7-nAChRs with IC50 of ~ 35 and 10 μM, respectively, and the maximal amplitude of inhibition of 30 – 50 %. EC50 of ACh at α3β4-nAChRs (~ 30 μM) was not changed in the presence of 35 μM ws-Lypd6, while the maximal amplitude of ACh-evoked current was reduced by ~ 20 %. Ws-Lypd6 did not elicit currents through nAChRs in the absence of ACh. Application of 1 μM ws-Lypd6 significantly inhibited (up to ~ 28 %) choline-evoked current at α7-nAChRs in rat hippocampal slices. Similar to snake neurotoxin α-bungarotoxin, ws-Lypd6 suppressed the long-term potentiation in mouse hippocampal slices. Colocalization of endogenous GPI-tethered Lypd6 with α3β4- and α7-nAChRs was detected in primary cortical and hippocampal neurons. Ws-Lypd6 interaction with the extracellular domain of α7-nAChR was modelled using ensemble protein-protein docking protocol. The interaction of all three Lypd6 loops (‘fingers’) with the entrance to the orthosteric ligand-binding site and the loop C of the primary receptor subunit was predicted. The results obtained allow us to consider Lypd6 as the endogenous negative modulator involved in the regulation of the cholinergic system in the brain.